2016
DOI: 10.1021/acs.chemrestox.6b00298
|View full text |Cite
|
Sign up to set email alerts
|

For Better or Worse, Iron Overload by Superparamagnetic Iron Oxide Nanoparticles as a MRI Contrast Agent for Chronic Liver Diseases

Abstract: Superparamagnetic iron oxide nanoparticles (SPIONs) have recently been used as an effective magnetic resonance imaging (MRI) contrast agent for the noninvasive diagnosis of chronic liver diseases including nonalcohol fatty liver diseases, nonalcohol steatohepatitis, and cirrhosis as well as liver tumors. However, the potential risk of the iron overload by SPIONs has been highly underestimated in chronic liver diseases. While most of SPIONs have been shown safe in the healthy group, significant toxicity potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…30,35 Thus, it was the disrupted iron homeostasis due to iron overload by SPION in cirrhosis that was a safety concern. 25,26 This was further supported by the reduced spleen weight observed aer 15 days with SPIO and PDL-SPION injections. It has been shown that the macrophages in the liver and spleen were mainly responsible for the uptake of SPIO and that it would take over 30 days in spleen to slowly convert SPIO into iron in ferritin.…”
Section: Improved Safety Prole Of N-phlip-spion In Cirrhosis Modelmentioning
confidence: 78%
See 2 more Smart Citations
“…30,35 Thus, it was the disrupted iron homeostasis due to iron overload by SPION in cirrhosis that was a safety concern. 25,26 This was further supported by the reduced spleen weight observed aer 15 days with SPIO and PDL-SPION injections. It has been shown that the macrophages in the liver and spleen were mainly responsible for the uptake of SPIO and that it would take over 30 days in spleen to slowly convert SPIO into iron in ferritin.…”
Section: Improved Safety Prole Of N-phlip-spion In Cirrhosis Modelmentioning
confidence: 78%
“…This was because although the poly-Llysine assembled SPION at 5 mg Fe per kg injection dose had no toxicity impact in healthy mice, signicant risk potential was discovered in cirrhosis model with disrupted liver function, lipid metabolism and iron level due to the iron overload post SPION injection, 25 which indicated the safety prole in cirrhosis was a more better safety study model. 26 Thus, the serum liver function markers and lipid cholesterol levels including alkaline phosphatase (AKP), aspartate aminotransferase (AST), alanine aminotransferase (ALT), total cholesterol, high-density lipid cholesterol (HDL) and low-density lipid cholesterol (LDL) were monitored in cirrhosis mice over 15 days post the intravenous injection of assembled SPION. Analysis of liver functional serum markers is much more accurate and indicative than the tissue pathological analysis, especial when the potential toxicity in cirrhosis is at the early stage.…”
Section: Improved Safety Prole Of N-phlip-spion In Cirrhosis Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasmall superparamagnetic iron oxide nanoparticles (USPION) are composed of magnetite (Fe 3 O 4 ) or maghemite (γ‐Fe 2 O 3 ) nanocrystals within a size range of 1‐50 nm diameter. These materials possess reactive surfaces and show unique superparamagnetic properties (strong magnetic response when an external magnetic field is applied) (Zhou & Wei, ). Owing to their high chemical reactivity, the surfaces of these particles can be modified to gain colloidal stability, facilitate their solubility in aqueous media, and improve their biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…SPION formulations are used in routine medical applications, despite research that indicates their harmful effects [ 180 ]. Chen et al [ 156 ] found that Ferucarbotran/Resovist had inhibitory effects on the osteogenic differentiation of mesenchymal cells and promoted cell migration and the expression of cell cycle and cancer signaling proteins, such as beta-catenin, SSX, and matrix metalloproteinase-2.…”
Section: Reviewmentioning
confidence: 99%